Rojo: el color del Perú - Beltrán-Suito, Rodrigo (Pontificia Universidad Católica del Perú, 2021)
The red color is characteristic of the symbols and emblems of Peru. It is not only present in the national flag, but is also characteristic of its national bird (Rupicola peruviana) and flower (Cantua buxifolia). Their color is due to the structural characteristics of organic substances belonging to the family of carotenoids and flavonoids. Apart from their use as colorants and pigments, these compounds also find diverse applications in pharmaceuticals and nutrition due to their antioxidant properties. This review details the specific compounds that give rise to the red color of the most representative plants and animals of Peru. The presence of unique substances not observed in other species is also highlighted.

El color rojo es característico de los símbolos y emblemas del Perú. No solamente está presente en la bandera, sino también es característico del ave (Rupicola peruviana) y flor (Cantua buxifolia) nacionales. Sus colores se deben a las características estructurales de las sustancias orgánicas pertenecientes a la familia de los carotenoides y flavonoides. Aparte de su uso como pigmentos y colorantes, estos compuestos también encuentran diversas aplicaciones en farmacéutica y nutrición debido a sus propiedades antioxidantes. Esta revisión detalla los compuestos específicos que dan origen al color rojo de las plantas y animales más representativos del Perú. Se destaca además la presencia de sustancias únicas no observadas en otras especies.
Red: the color of Peru
Keywords: Carotenoides; Flavonoides; Química del color; Productos naturales; https://purl.org/pe-repo/ocde/ford#1.04.00